JENIS-JENIS BAMBU DI BUKIT GUNUNG ANGGAS, DESA SIDING, KECAMATAN SIDING, KABUPATEN BENGKAYANG - Yuliati Indrayani; Lolyta Sisillia; mailing mailing (JURNAL HUTAN LESTARI, 2022)
Gunung Anggas Hill, Siding Village, Siding Subdistrict, Bengkayang District has many wildly bamboo plants. Bamboo is a type of grass that belongs to the Gramineae family and is one of the non-timber forest product commodities that grows in most forests in Indonesia and other tropical countries. Bamboo is categorized as a versatile non-timber forest product. Besides being useful, several species of bamboo are ornamental plants as well as processing waste filtering and preventing erosion. This study aims to determine the bamboo species and make a map of the distribution of bamboo based on the coordinates of Gunung Anggas Hill, Siding Village, Siding Subdistrict, Bengkayang District. This study was conducted use a survey method, namely the implementation of path exploration to obtain all species of bamboo. Exploration is carried out directly, such as recording and identifying plants in each encounter on the right and left at three altitudes (100, 200, and 300 masl) with a path length of 100 meters on the hiking trail. The results found four genera of bamboo (Dendrocalamus, Schizostachyum, Bambusa, and Gigantochloa) and eight species of bamboo such as Petung Bamboo (Dendrocalamus asper), Kayan Bamboo (Schizostachyum flexuosum Widjaja), Aur Bamboo (Bambusa vulgaris var. vulgaris), Lemang Bamboo (Schizostachyum brachycladum Kurz), Tamiang bamboo (Schizostachyum latifolium), Tarenk Bamboo (Gigantochloa hasskarliana (kurz) Backer ex Heyne), Mayan bamboo (Gigantochloa robusta) kurz., Timiang pogok bamboo (Schizostachyum silicatum).Keywords: bamboo species, different altitude, Siding VillageAbstrakBukit Gunung Anggas Desa Siding, Kecamatan Siding, Kabupaten Bengkayang memiliki banyak tanaman bambu yang tumbuh secara liar. Bambu adalah salah satu jenis rumput-rumputan yang termasuk kedalam family Gramineae dan merupakan salah satu komoditas hasil hutan bukan kayu yang tumbuh disebagian besar hutan Indonesia dan negara tropika lainnya. Bambu dikategorikan sebagai hasil hutan bukan kayu yang serbaguna. Selain berguna beberapa jenis bambu merupakan tanaman hias maupun pengolah penyaringan limbah dan pencegah erosi. Penelitian ini bertujuan untuk memperoleh nama jenis bambu dan membuat peta persebaran bambu berdasarkan titik koordinat yang ada di Gunung Anggas Desa Siding, Kecamatan Siding, Kabupaten Bengkayang. Penelitian ini menggunakan metode survei, yaitu pelaksanaannya secara eksplorasi jalur untuk memperoleh semua jenis bambu. Eksplorasi dilakukan secara langsung, yaitu mencatat dan mengidentifikasi tumbuhan setiap perjumpaan disebelah kanan dan kiri pada masing-masing ketinggian (100, 200, dan 300 mdpl) dengan panjang jalur penelitian 100 meter di jalur pendaki. Hasil survey menemukan empat Genus bambu (Dendrocalamus, Schizostachyum, Bambusa, dan Gigantochloa) dan delapan sepesies bambu yaitu Bambu Petung (Dendrocalamus asper), Bambu Kayan ( Schizostachyum  flexuosum Widjaja ), Bambu Aur (Bambusa vulgaris var. vulgaris), Bambu Lemang (Schizostachyum brachycladum Kurz), Bambu tamiang (Schizostachyum latifolium), Bambu Tarenk (Gigantochloa hasskarliana (kurz) Backer ex Heyne), Bambu Mayan (Gigantochloa robusta) kurz., Bambu temiang pogok (schizostachyum silicatum).Kata Kunci : Spesies bambu, ketinggian berbeda, Desa Siding